Kontribusi Mahasiswa dalam Program Pembersihan Sungai Kampus dan Implikasinya pada Kesadaran Lingkungan dan Kualitas Air - Laili Mas Ulliyah Hasan; Nur Farida Adzawiyah; Mirza Elmy Safira; Eli Masnawati; Wakid Evendi (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The river cleanup program conducted by students is a strategic ecological initiative to reduce pollution and increase environmental awareness. This Community Service (PkM) activity aims to identify the role of students in cleaning rivers around the campus and its impact on environmental awareness and the physical condition of the water. The method used is a descriptive approach based on Asset Based Community Development (ABCD) through the stages of identifying environmental assets and potential, participatory mapping with the community, implementing cleanup actions, and evaluating the results of the activity. Data were obtained through field observations and documentation of activities. The results of the PkM show that students and the community are directly involved in identifying pollution points, collecting and sorting waste, and providing waste management education to local residents. Routine activities result in a decrease in the volume of surface waste, smoother river flow, and increased water clarity based on visual observations. Joint participation also increased community involvement in maintaining the cleanliness of the riverbanks. Thus, this community service activity achieved its goals of increasing concrete actions in river cleanups and encouraging active community participation in environmental conservation efforts.